Methods of Organizing Mental Arithmetic Lessons in Preschool Education - Sobirova Mohinur (Researchparks Publishing, 2022)
Dear reader, In this article, we are talking about one of the most convincing and effective sciences today, namely in the field of mental arithmetic. This subject is currently being studied by many teachers and additional classes are being held for primary school students in schools. At present, most of the additional classes in these schools are registered and the Republican Olympiads are held. As a sup plement to this subject, the preschool education system is currently teaching in almost 30% of pre-school educational institutions of the country, and it is giving good results. Our goal is to further develop this field and to form a system of teaching this subject in all preschool educational institutions of the Republic. This article provides brief information about the science of mental arithmetic.